Pengaruh Rebranding Dan Brand Image Terhadap Keputusan Pembelian Produk Kosmetik Dan Skincare Hanasui Di Jakarta Barat - Hasanah, Nurul; Rini, Ratih Setyo (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
ABSTRACT Abstract - This study aims to determine the effect of rebranding and brand image on purchasing decisions for Hanasui cosmetics and skincare products in West Jakarta, both partially and simultaneously. The research method used a quantitative approach with a survey technique. A sample of 100 respondents was selected using purposive sampling and analyzed using multiple linear regression with the help of SPSS version 27. The t-test results indicate that rebranding (t = 5.482; sig. < 0.001) and brand image (t = 7.166; sig. < 0.001) have a significant partial effect on purchasing decisions. The F test produced a calculated f value of 178.016 > f table 3.09 with sig. < 0.05, indicating that both variables have a significant simultaneous effect. The Adjusted R² value of 0.781 shows that 78.1% of the variation in purchasing decisions is influenced by Rebranding and brand image. This study confirms that brand image has a dominant influence on purchase decisions compared to Rebranding. These results reinforce the importance of visual identity consistency and positive brand perception in shaping consumer behavior. Keywords: Rebranding, Brand image, Purchase Decision